THE EFFECT OF ORAL HYGIENE WITH CHLORHEXIDINE ON THE INCIDENCE OF VENTILATOR-ASSOCIATED PNEUMONIA (VAP) IN PATIENTS ON VENTILATION IN THE INTENSIVE CARE UNIT - Sutrisno; Deny Eko Saputro; Mayta Sari Dwianggimawati (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Ventilator Associated Pneumonia (VAP) is a nosocomial infection that often occurs in patients with mechanical ventilation and can increase the risk of complications and mortality. This study aims to analyze the effect of oral hygiene with chlorhexidine on the incidence of VAP in patients with ventilators. The study design used a pre-experimental approach with a one-group pretest–posttest approach. A sample of 15 patients was selected using purposive sampling. Oral hygiene intervention with chlorhexidine was given twice a day for 3 days. The incidence of VAP was measured using the Clinical Pulmonary Infection Score (CPIS). Data analysis used the Wilcoxon Test. The results showed that the average body temperature decreased from 37.69°C to 37.21°C (p=0.028). Leukocyte values ​​showed a tendency for improvement after the intervention. Tracheal secretions did not show significant changes (p=1.00). The mean PaO₂/FiO₂ ratio changed from 241.6 to 236.1 (p=0.048). Chest X-ray evaluation results showed an improvement in pulmonary infiltrates in some respondents after the intervention. Overall, CPIS scores showed a downward trend after oral hygiene with chlorhexidine. Routine and standardized implementation of this measure has the potential to improve the quality of nursing care and reduce the risk of complications in patients on mechanical ventilation.